1989
DOI: 10.2307/1937537
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework for Data Analysis of Wind Dispersal of Seeds and Pollen

Abstract: We compared a variety of models for the analysis of data on the wind dispersal of seeds and pollen. Dispersal distances from a source depend upon such factors as settling velocity, height of release, wind speed and turbulence, and specific morphological adaptations for dispersal. The dispersal curve, which describes the frequency distribution of dispersal distances, usually shows its peak at some distance from a source and falls off with distance. We used the location of that peak as a measure of dispersal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
332
2
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(351 citation statements)
references
References 28 publications
(16 reference statements)
10
332
2
6
Order By: Relevance
“…A common explanation of this fact is that a reduction in canopy density can enhance within-stand air movements (Okubo and Levin, 1989) and pollen being carried over larger distances (Di-Giovanni and Kevan, 1991;Lindgren et al, 1995). However, the pollen dispersal distances obtained in our study for Talayuelas (d ¼ 174.4 m and 1068 trees per hectare) and Landete (d ¼ 78.4 m and 810 trees per hectare) were not consistent with this hypothesis.…”
Section: Discussioncontrasting
confidence: 75%
“…A common explanation of this fact is that a reduction in canopy density can enhance within-stand air movements (Okubo and Levin, 1989) and pollen being carried over larger distances (Di-Giovanni and Kevan, 1991;Lindgren et al, 1995). However, the pollen dispersal distances obtained in our study for Talayuelas (d ¼ 174.4 m and 1068 trees per hectare) and Landete (d ¼ 78.4 m and 810 trees per hectare) were not consistent with this hypothesis.…”
Section: Discussioncontrasting
confidence: 75%
“…To understand the evolution of wind dispersal, some models have been proposed based on physical factors that affect the aerodynamic ability of diaspores, such as wind speed and direction and height of release (Okubo & Levin 1989;Levin et al 2003). Different diaspores formats respond unequally to these factors, which act as selective pressures in the anemochorous fruits and seeds, since they influence the distance they are transported (Levin et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The same spatial and demographic features peculiar to small isolated stands, which pose evident experimental advantages, must be carefully considered as factors conditioning target reproductive processes. Airborne pollen dynamics in forested areas may be highly affected by wind turbulences associated with horizontal and vertical canopy structure (Di-Giovanni and Kevan, 1991), and it has been suggested that low-density populations may enhance pollen movement (Okubo and Levin, 1989). However, the study site is located within a uniform, flat and continuous forest of several thousand hectares.…”
Section: Discussionmentioning
confidence: 99%